The Treaty of Waitangi and the Control of Language by R Dawson - Opie, Joss (Victoria University of Wellington Law Review, 2001)
Richard Dawson The Treaty of Waitangi and the Control of Language (Institute of Policy Studies, Wellington, 2001). Paperback, 255 pages, $NZ29. This article is a book review of Richard Dawson's The Treaty of Waitangi and the Control of Language. In his book, Dawson argued that there was a Crown monopoly over the language of the Treaty. Therefore, Dawson called for a balanced dialogue between the Crown and Māori. However, Opie argues that such a binary description of power is problematic and instead adopts Michel Foucault's bottom-up description of power which allows for a more nuanced view of the respective identities of the Crown and Māori.